ORGANIZATIONAL CHANGE MANAGEMENT IN REGULATED ENVIRONMENTS: CHALLENGES AND SOLUTIONS - de Souza Rocha, Ingrid Augusta (Revista Sistemática, 2020)
Organizational change management (OCM) in regulated environments presents unique challenges due to strict compliance requirements, complex processes, and the need for alignment across multiple stakeholders. This paper examines the key obstacles faced by organizations operating under regulatory constraints and identifies strategies to effectively implement change. Drawing from empirical studies and industry practices, the study highlights the importance of structured change frameworks, communication, stakeholder engagement, and technological support. The findings demonstrate that successful OCM in regulated settings requires balancing compliance adherence with operational agility to achieve sustainable organizational transformation.